Pelaksanaan Analisis Soal Oleh Guru Sebagai Kegiatan Evaluasi Pembelajaran Seni Tari Di SMA N 3 Payakumbuh - Dian Tri Marwanti Kusumaning Tyas; Yos Sudarman (FBS Universitas Negeri Padang, 2021)
This study aims to explain the implementation of analysis of semester exams by teachers as an evaluation of cultural arts (dance) learning at SMA Negeri 3 Payakumbuh. This type of research is qualitative research with a descriptive approach to analysis. The main instrument in this study was the researcher himself and assisted with supporting instruments such as stationery and cameras. Data collection techniques are conducted by means of observation, interview and literature studies. The steps of analyzing data are collecting data, describing data and concluding data. The results showed that the analysis of the problem items conducted by art and culture teachers at SMA Negeri 3 Payakumbuh, can be said as an extra activity (additional) curriculum because the activity of analysis of the point of this question is an activity outside the mandatory duties of teachers in schools. Of the 15 cultural arts (dance) questions that have been analyzed in mgmp discussion forums and observer participants discussions with teachers, it was determined that 8 questions should be replaced for reasons that do not fit the material and the choice of answer options that confuse students later. From the activities and results of analysis of questions like this, teachers have conducted qualitataif analysis of questions only from the construction aspect (how the problem was built) and the content aspect (how the material conformity) of the question analyzed. But the analysis of the problem that teachers do quantitatively is not done.